2005
DOI: 10.1097/01.ico.0000154402.01710.95
|View full text |Cite
|
Sign up to set email alerts
|

Altered Corneal Nerves in Aqueous Tear Deficiency Viewed by In Vivo Confocal Microscopy

Abstract: Abnormal morphologic changes are observed in aqueous tear deficiency that are more severe in Sjögren syndrome. The distinct changes of corneal nerves include increased nerve number, tortuosity, and chances of branching, suggesting an attempted nerve regeneration. A strong correlation exists between the changes of nerve morphology and the degree of dry eye. These results provide some possible evidence for the abnormal corneal sensation in dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
102
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(119 citation statements)
references
References 40 publications
9
102
3
5
Order By: Relevance
“…However, there is not agreement regarding IVCM findings in the literature. When evaluating sub-basal nerve density, some authors observed a decrease (2-10, 33, 34), while others found no change (35,36), or, in accordance with our study, an increase in density (37). However, most of these studies were conducted on groups with unequal numbers of patients with SSDE and NSSDE, making the comparison between studies difficult.…”
Section: Discussioncontrasting
confidence: 40%
See 4 more Smart Citations
“…However, there is not agreement regarding IVCM findings in the literature. When evaluating sub-basal nerve density, some authors observed a decrease (2-10, 33, 34), while others found no change (35,36), or, in accordance with our study, an increase in density (37). However, most of these studies were conducted on groups with unequal numbers of patients with SSDE and NSSDE, making the comparison between studies difficult.…”
Section: Discussioncontrasting
confidence: 40%
“…However, previous literature does not show a unique relationship between these aspects and, most articles emphasize a scant association between the signs and symptoms in DE disease (28)(29)(30)37), while few others report occasional associations (2,31) or inverse correlations (32). Such heterogeneous data are probably due to the small sample size used in many past studies, and because of the characteristics of the different questionnaires used.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations